Polar rectification effect in electro-fatigued SrTiO3-based junctions - Xu, Xueli; Zhang, Hui; Zhong, Zhicheng; Zhang, Ranran; Yin, Lihua; Sun, Yuping; Huang, Haoliang; Lu, Yalin; Lu, Yi; Zhou, Chun; Ma, Zongwei; Shen, Lei; et al. (ACS applied materials & interfaces, 2020)
Rectifying semiconductor junctions are crucial to electronic devices. They convert alternating current into a direct one by allowing unidirectional charge flows. Analogous to the current-flow rectification for itinerary electrons, here, a polar rectification that is based on the localized oxygen vacancies (OVs) in a Ti/fatigued-SrTiO3 (fSTO) Schottky junction is first demonstrated. The fSTO with OVs is produced by an electrodegradation process. The different movabilities of localized OVs and itinerary electrons in the fSTO yield a unidirectional electric polarization at the interface of the junction under the coaction of external and built-in electric fields. Moreover, the fSTO displays a pre-ferroelectric state located between paraelectric and ferroelectric phases. The pre-ferroelectric state has three sub-states and can be easily driven into a ferroelectric state by an external electric field. These observations open up opportunities for potential polar devices and may underpin many useful polar-triggered electronic phenomena.
Gesehen am 02.09.2020